(untitled) (De Musica, 2023)
Charlie Haden is one of the most important musicians in the history of jazz. Both as a double bassist and composer, he innovated the musical language of the jazz and free jazz scene from the 1960s onward. His particular sound and his original vision of music have enabled him to play with the greatest musicians in the history of jazz, making himself always recognizable, even in different musical contexts. His political activism led him to clash with regimes all over the world, even going so far as to be imprisoned in Portugal in 1971. This article will analyze several performances of Haden’s compositions and fragments of solos, showing recurring elements and stylistic differences dictated by the ensemble or the peculiarities of the individual artists on the recordings, as well as linking the genesis of the pieces (as with Song for Che) to Haden’s own extra-musical ideas.